Corporate Lobbying and Commitment Failure in Capital Taxation - Marceau, Nicolas; Smart, Michael (American Economic Review, 2003)
This paper investigates the effects of lobbying by corporations when investments are irreversible and government cannot commit to tax policies. We show that industries which rely more heavily on sunk capital lobby more vigorously and are generally more successful in obtaining tax breaks. Thus lobbying can mitigate the capital levy problem. Nevertheless, these industries invest less in long-run equilibrium than more flexible ones. We then consider the effects of relaxing legal restrictions on corporate lobbying. When the deadweight costs of lobbying fall, taxes on sunk capital tend to fall, but political contributions may rise, as lobbyists compete more intensively for political favors. On balance, a ban of lobbying may therefore cause investment to rise or fall.(This abstract was borrowed from another version of this item.)